Correlates of population genetic differentiation in marine and terrestrial environments. (28th September 2018) - Schiebelhut, Lauren M.; Dawson, Michael N
Abstract: Aim: Theory predicts that differences in phylogeographic structure between species should be related to differences in life history, environment, and evolutionary time. Reviews of empirical studies suggest sometimes complex interactions and possibly a preponderance of exceptions to the predicted relationship that greater population genetic differentiation results from lower dispersal potential, as a function of life history. We apply an analytical framework, which controls for effects of environment and time, to test the hypothesis that contrasts in population genetic differentiation are proportional to contrasts in life history traits. Location: Global. Methods: We conducted a meta‐analysis using contrasts of life history traits and population genetic differentiation between synchronously diverging codistributed (SDC) taxa. Because SDC taxa experienced the same environment at the same time, the effects of time and environment are effectively controlled when analysing other causes of genetic differentiation within SDC taxa. This offers the opportunity to rigorously test whether traits favouring greater dispersal potential—such as fecundity, census population size, and duration of the dispersive stage—do lead to lower population genetic differentiation. Results: We find a strong inverse relationship between dispersal potential and population genetic differentiation, consistent with predictions. SDC species pairs with similar dispersal potential show similar population genetic differentiation; species with higher dispersal potential have lower population genetic differentiation, relative to species with lower dispersal potential. Main conclusions: SDC comparisons provide a rigorous method for disentangling the factors driving patterns of genetic differentiation in the marine and nonmarine realms. We found broad support for the relationship that higher dispersal potential is associated with lower population genetic differentiation, the specifics of which can be influenced by place, time, and taxon. This relationship appears to be stronger on land than in the sea. However, many factors influence population genetic structure; deviations in measured versus predicted population genetic differentiation may indicate the influence of drift or selection. Too often, too many factors go unmeasured, constraining our ability to disaggregate dispersal syndromes and fully resolve the influence of specific life history characteristics on gene flow.